Devolution as a threat to democratic-decision making in forestry?: findings from three states in India - Sarin, M.; Singh, N.M.; Sundar, N.; Boghal, R.K. (Overseas Development Institute, 2003)
This paper looks at two interfacing trends shaping devolution of forest management in India: i. appropriation of space for forest management by diverse self-initiated community formations at the grass roots level despite state seizure of forests ii. state-driven devolution where government policies define the scope of local authority in forest management. The paper assesses whether state devolution policies are increasing or decreasing space for exercising democratic control over forest decisions, enhancing livelihoods and improving forest quality. This paper is based on research studies undertaken in three states, Orissa, Madya Pradesh and Uttarakhan region of Uttar Pradesh. It concludes that meaningful devolution requires nurturing democratic, self-dependent women and men to make real choices for enhancing sustainable livelihoods in accordance with their own priorities. This needs to be accompanied by holistic forest sector reform processes with multi-sectoral and multi-stakeholder participation in the context of the growing threats posed by market-driven globalisation to genuine devolution and democratisation.